2011
DOI: 10.1891/1933-3196.5.3.111
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movement Desensitization and Reprocessing in Counseling a Male Couple

Abstract: This practice-based article discusses the use of eye movement desensitization and reprocessing (EMDR) in counseling "Paul" and "Eddie" (aliases), a couple for 4 years who presented with what they identified as "communication problems." Through the use of psychosocial assessments of the men's personal histories, it was determined that Paul's experience of feeling controlled and Eddie's struggles to believe that he mattered in the relationship were linked to traumatic memories in each man's childhood that relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…EMDR in the conjoint couple context may be more clinically effective in certain cases than separating participants for EMDR or referring each to their individual EMDR therapist. Related research and published case examples (Capps et al, 2005;Capps, 2006;Flemke & Protinsky, 2003;Knox, 2016;Legg, 2013;Moses, 2003Moses, , 2007Reicherzer, 2011;Snyder, 1996) have consistently suggested that conjoint EMDR can expand intimacy between partners, which is consistent with findings in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…EMDR in the conjoint couple context may be more clinically effective in certain cases than separating participants for EMDR or referring each to their individual EMDR therapist. Related research and published case examples (Capps et al, 2005;Capps, 2006;Flemke & Protinsky, 2003;Knox, 2016;Legg, 2013;Moses, 2003Moses, , 2007Reicherzer, 2011;Snyder, 1996) have consistently suggested that conjoint EMDR can expand intimacy between partners, which is consistent with findings in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Capps (2006) combined EMDR with Gestalt therapy. Reicherzer (2011) wrote about using EMDR therapy with a gay couple in conjoint therapy. Other EMDR therapists have reported therapeutic gains with the use of EMDR in couples therapy (Flemke & Protinsky, 2003;Protinsky, Sparks, & Flemke, 2001;Snyder, 1996).…”
Section: Couple Therapy With Emdrmentioning
confidence: 99%